CORPORATE TRAINING: FROM PLANNING TO EFFICIENCY - Pudovina, Anastasia; Mamatelashvili, Olga; Mukhamadieva, Elvira; Shaybakova, Emma; Bayrushina, Florida (Revista Inclusiones, 2020)
The urgency of the studied problem is conditioned by the level and pace of the modern business development that have fundamentally changed the attitude to the training system as a service and an integral part of the personnel development process. The absolute imperative of the modern socioeconomic development of society is the continuous growth of the intellectual and creative potential of a man. One of the main factors of this growth is the effective modernization of Russian education in general and corporate education in particular. The purpose of the study is to assess the effectiveness of corporate training: planning, identifying and structuring the factors of the company’s external and internal environment, directly or indirectly related to training the company’s employees (identifying the untapped, not fully utilized resources of the corporate training capacity, as well as economic security, risks, explicit and hidden threats to the corporate training effectiveness increase). The article is aimed at searching the ways to further develop corporate training, meet its modern requirements of a market economy, working ahead of its competitors, and also change the attitude of specialists to their work on the basis of optimally planned (developed) programs, involving the hidden resources of the company and the individual. The leading approach to the study of this problem is an analytical method that allows analyzing the works of Russian and foreign scientists in the field of management in education, from identifying the essence of this category to the study of the corporate training state in corporations. The study of this problem is impossible without the use of scientific methods such as analysis and synthesis, as well as systematization and typology, since education appears as a system object, the study of which involves not only the analysis of education as a specific socio-economic phenomenon but also as a type of entrepreneurial activity.